2021
DOI: 10.3389/fimmu.2021.736260
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Pathways Altered in Frontotemporal Dementia With Autoimmune Disease

Abstract: Behavioral variant frontotemporal dementia (bvFTD) is a younger onset form of neurodegeneration initiated in the frontal and/or temporal lobes with a slow clinical onset but rapid progression. bvFTD is highly complex biologically with different pathological signatures and genetic variants that can exhibit a spectrum of overlapping clinical manifestations. Although the role of innate immunity has been extensively investigated in bvFTD, the involvement of adaptive immunity in bvFTD pathogenesis is poorly underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…In addition, the possible pathogenesis of Fam20C in coronary artery disease has been revealed, of which the Fam20C-dependent phosphorylation of sortlin at Ser825 is integral in the process of smooth muscle cell (SMC) calcification ( Goettsch et al, 2016 ). One latest study reported the decreased expression of Fam20C in behavioral variant frontotemporal dementia (bvFTD) with autoimmune disease ( Bright et al, 2021 ).…”
Section: Diseases Associated With Fam20cmentioning
confidence: 99%
“…In addition, the possible pathogenesis of Fam20C in coronary artery disease has been revealed, of which the Fam20C-dependent phosphorylation of sortlin at Ser825 is integral in the process of smooth muscle cell (SMC) calcification ( Goettsch et al, 2016 ). One latest study reported the decreased expression of Fam20C in behavioral variant frontotemporal dementia (bvFTD) with autoimmune disease ( Bright et al, 2021 ).…”
Section: Diseases Associated With Fam20cmentioning
confidence: 99%
“…Specific O- GlcNAc modifications are important for T cell activation and their blocking reduces IL-2 production and cell proliferation ( 82 ). Changes in O -glycan composition are associated with different metabolic conditions and disorders, including autoimmune diseases, type II diabetes, and cardiovascular diseases ( 83 , 84 ). O -glycans are present in high concentrations in the zona pellucida surrounding mammalian eggs and play critical roles in fertilization ( 85 ).…”
Section: Discussionmentioning
confidence: 99%